BOOK REVIEWS (Bioethics, 1990)
Abating Treatment With Critically III Patients: Ethical and Legal Limits to the Medical Prolongation of Life, by Robert F. Weir Birthrights: Law and Ethics at the Beginning of Life, Robert Lee and Derek Morgan (eds.) Tomorrow's Child: Reproductive Technologies in the 90's by Lynda Birke